Phillip collective hubb : architecture as a catalyst for socioeconomic and spatial equality in Cape Town - Malan, Jeanneke (School of Architecture, Planning and Geomatics, 2017)
Sixteen years after the abolition of apartheid, South African society may be democratic and free, but do all persons live together in harmony and with equal opportunities? The initial interest of the M Arch (Professional) Architectural Project is the issue of persistent socioeconomic and spatial segregation and inequality in South African society and cities today, and the role architecture can play towards socioeconomic and spatial transformation. South African cities, looking at Cape Town in particular, are faced with many problems common to developing countries. These include an increase in population, rapid urbanisation, poverty, homelessness, joblessness, inadequate resources, meagre living conditions in informal settlements and poorly functioning and unsustainable urban settlements that do not function to benefit the population as a whole. In addition to these problems is the issue of segregation amongst people from different socioeconomic, class, cultural and racial backgrounds. This stems from a long and complex history dating as far back as colonial times through to the apartheid era, the effects of which are deeply embedded in post-colonial and post-apartheid South African societies and urban environments. Architecture and planning played an intrinsic role in the spatial manifestation of the apartheid regime, and to some extent contemporary architectural projects continue to ensure apartheid's legacy. Architecture thus, in response, holds the potential to initiate a shift towards socioeconomic and spatial equality in South Africa today.